PERAN GURU PROFESIONAL DAN PEMBELAJARAN INKUIRI DALAM MENGHADAPI TANTANGAN MASYARAKAT EKONOMI ASEAN (MEA) - Maya Meilia; Nova Pratiwi (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
The main challenge is now the ASEAN free trade area or Asean Economic Community for education, to prepare quality human resources. Guru is one of the parties, which are crucial for preparing human resources to compete and adapt to global developments. Teachers are required to meet the standards of competence, namely: pedagogical, professional, and social personalities in addition, teachers must actively for training, seminars, research, and continuing education. In an effort to provide the best learning experience for students, one of the effective models that should be controlled by the teacher, is learning inquiry, which has four methods that can be applied in accordance with the demands of teaching material competence, namely; confirmation of the investigation, structured, guided and open inquiry. Methods of investigation are very suitable to be applied to the material abstract and mathematical formulas though, experience researching the problem, improve the ability to think critically and creatively and expanding the horizons of students. The main challenge is now the ASEAN free trade area or Asean Economic Community for education, to prepare quality human resources. Guru is one of the parties, which are crucial for preparing human resources to compete and adapt to global developments. Teachers are required to meet the standards of competence, namely: pedagogical, professional, and social personalities in addition, teachers must actively for training, seminars, research, and continuing education. In an effort to provide the best learning experience for students, one of the effective models that should be controlled by the teacher, is learning inquiry, which has four methods that can be applied in accordance with the demands of teaching material competence, namely; confirmation of the investigation, structured, guided and open inquiry. Methods of investigation are very suitable to be applied to the material abstract and mathematical formulas though, experience researching the problem, improve the ability to think critically and creatively and expanding the horizons of students.